Pengaruh Variasi Jenis Bahan Terhadap Pengurangan Taraf Intensitas Bunyi - Sandi, Dala Novika; Wahyuni, Dwiria; Nurhasanah, Nurhasanah; Muliadi, Muliadi; Hasanuddin, Hasanuddin; Nurhanisa, Mega (Jurnal Fisika Unand, 2023)
Acoustic materials such as plastic carpet, gypsum board, styrofoam and plywood can be used to reduce sound intensity. Nevertheless, the existing research has generally focused on single-ingredient studies. In this research, the optimum thickness of each material will be sought based on its efficiency in reducing the sound intensity level. Besides that, the efficiency of various types of materials will also be tested for reducing the level of sound intensity. In this study, a resonator tube was used in making measurements. Acoustic materials used as test materials, both single materials and combined materials, can be placed in the resonator tube. The distance between the sound source and the detector is 30 cm, with the position of the detector right behind the acoustic material. Tests on a single material show that the measured sound intensity level decreases in proportion to the thickness of the acoustic material, with styrofoam has the lowest efficiency. Meanwhile, the combined material that combines plastic carpet material at a frequency of 2000 Hz has an efficiency value that tends to be higher than the combination of materials without carpet with efficiency >30%. However, at a frequency of 1500 Hz, all combined materials have efficiency values that are not significantly different. All models of material combinations are proven to be able to reduce sound intensity levels compared to single materials. Thus, it can be concluded that the combined material has the potential as an efficient acoustic material.